Master’s Level Teacher Preparation for Educating Immigrant Students with Special Needs in US Schools - Hoover, John J.; Smith-Davis, Judy; Baca, Leonard; Love, Emily Wexler (Journal of the American Academy of Special Education Professionals, 2008)
This article provides results from a research project investigating how Master’s level teacher training programs address the education of immigrant students at-risk and those with special needs. We surveyed Master’s programs in nine states with significant populations of immigrant students. Results suggest that graduate level programs in special education emphasize selected immigrant special education training and competency areas to a limited-moderate degree. Our findings reveal that teacher training was similar among schools that differed in size and type of degree granting institution (Master’s vs. Master’s and Doctoral). Within-school analyses found the training area of Assessment was emphasized the most while training in Collaboration was the least emphasized. We share results from this study and also provide suggestions for future research.